The plains of passage - Auel, Jean M. (Bantam Books, 1991)
The sequel to The Mammoth Hunters finds Ayla and Jondalar on their long journey returning to Jondalar's family. Returning humankind's earliest days, the fourth novel in the Earth's Children series. Courageous heroine Ayla and companion Jondalar leave the Mammoth Hunters and travel into the dark, spectacular lands of an unmapped world-always driven to reach a place that they can finally call home.